Buzz Boy and Fly Guy - Arnold, Tedd. (New York : Scholastic, 2010)
Buzz creates a comic book that features Buzz Boy and Fly Guy as the superheroes.
"Cartwheel books."
1.5
K-3
K-3
Keywords: Flies -- Juvenile fiction; Superheroes -- Juvenile fiction; Flies -- Fiction; Superheroes -- Fiction; Flies -- Fiction; Superheroes -- Fiction